Development of an Interactive HOTS Gamified e-Module for Prospective Elementary School Teachers at the University Level - Nursyaida Nursyaida; Pratiwi Samad (Journal Emerging Technologies in Education, 2024)
Background. The crritical thinking and creativity designing has not been applied and adopted in learning optimally. The HOTS e-modul learning for teacher training program will lead them to analize and maximize their learning achivment. The purpose of learning need to be improved as well as the conventional media design must be updated to help learners to teach creatively and hink critically. Purpose. The purpose of this study is to develop HOTS content in the science subject e-module of Pohuwato University, increase creativity in developing teaching strategies and methods, improve critical thinking in understanding learning content and develop the creativity of prospective teachers in designing materials, media and teaching modules that are in accordance with the conditions and abilities of students at the elementary school level. Method. The method used is R&D with the DDDE (Decide, Design, Develop, and Evaluate) model which was chosen because it is in accordance with the purpose of developing HOTS-based interactive e-modules and gamification. The small-scale trial of the HOTS E-module was carried out by experts of teacher, lecturers and also a large-scale trial was carried out by 46 students. The test subject was determined using the purposive sampling technique. In collecting research data, it is carried out by providing questionnaire tests that have been collected descriptively. Results. Results shows that the interactive HOTS e-module based on gamification, developed using the DDD-E model, meets the validity criteria with an average score of 3.89, is deemed practical with an average score of 3.66, and demonstrates effectiveness, with 86.8% of students achieving a minimum test score of 70. Conclusion. The interactive HOTS e-module, developed using the DDD-E model, is valid, practical, and effective. It equips future teachers with innovative tools to enhance critical thinking and student engagement, promoting better learning outcomes through gamified educational experiences.